2013
DOI: 10.1016/j.cellimm.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells upregulate CD69 after coculture with xenogeneic genetically-modified pig mesenchymal stromal cells

Abstract: Mesenchymal stromal cells (MSC) obtained from α1,3-galactosyltransferase gene knock-out pigs transgenic for the human complement-regulatory protein CD46 (GTKO/CD46 pMSC) suppress in vitro human anti-pig cellular responses as efficiently as allogeneic human MSC. We investigated the immunoregulatory effects of GTKO/CD46 pMSC on human CD4+ and CD8+ T cell proliferation in response to pig aortic endothelial cells (pAEC). pMSC efficiently suppressed T cell proliferation, which was associated with downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…However, the immunosuppressive regimens utilized in most of these studies would currently not be clinically applicable (mainly because they included an anti‐CD154mAb), and therefore, present studies are aimed toward reducing the intensity of the regimen and ensuring that all agents administered are approved for clinical use. Genetic manipulation of the pig to increase the resistance of the islets to the primate T‐cell response is a potential option, as is the cotransplantation of islets with mesenchymal stromal cells or Sertoli cells .…”
Section: Cell and Tissue Xenotransplantationmentioning
confidence: 99%
“…However, the immunosuppressive regimens utilized in most of these studies would currently not be clinically applicable (mainly because they included an anti‐CD154mAb), and therefore, present studies are aimed toward reducing the intensity of the regimen and ensuring that all agents administered are approved for clinical use. Genetic manipulation of the pig to increase the resistance of the islets to the primate T‐cell response is a potential option, as is the cotransplantation of islets with mesenchymal stromal cells or Sertoli cells .…”
Section: Cell and Tissue Xenotransplantationmentioning
confidence: 99%
“…From the studies summarized in this brief review, and from other studies [1215], we have concluded that:- (i) isolation of MSCs from genetically-modified pigs is efficient; (ii) expression of surface MSC markers and poor expression of SLA and costimulatory molecules can be demonstrated; (iii) tri-lineage differentiation can be achieved; (iv) pMSCs have low xenoantigenicity and also an inhibitory effect on human T cell xenoresponses; (v) GTKO/CD46 pMSCs downregulate human T cell proliferation as efficiently as hMSCs; and (vi) cell-cell contact appears to be required for the MSCs to have their immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…At our own center, we have successfully harvested and cultured MSCs from pig bone marrow and adipose tissue [1215]. We identified a fibroblast-like morphology of genetically-engineered porcine adipose-derived MSCs (Figure 1).…”
Section: Pig Mesenchymal Stromal Cells (Pmscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. showed that GT‐KO/CD46 pMSC suppressed both CD4 + and CD8 + human T‐cell proliferation in response to PAEC, associated with a downregulation of granzyme B expression. No induction of CD4 + CD25 + Foxp3 hi regulatory T cells or T‐cell apoptosis was detected.…”
Section: Immunobiologymentioning
confidence: 99%